Accessory Lesser Metatarsal Sesamoids in All of the Metatarsophalangeal Joints A Case Report - (:unkn) unknown (AMER PODIATRIC MED ASSOC, 2017)
Lesser metatarsal sesamoids are one of the most common accessory bones of the foot and are most commonly seen at the fifth metatarsophalangeal joint. They are rarely seen in other metatarsophalangeal joints. In the literature, there are reports of solitary accessory sesamoid bones seen at lesser metatarsophalangeal joints. We report the case of a 68-year-old woman with lesser metatarsal sesamoids accompanying all of the metatarsophalangeal joints.
Keywords: MOMENT; BONES